2017
DOI: 10.1093/occmed/kqx048
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis with acute tubular necrosis following occupational inhalation of thinners

Abstract: Thinners are mixtures of organic solvents commonly containing toluene, xylene, acetone, hexane, benzene and methyl isobutyl ketone. This report describes a case of rhabdomyolysis with acute tubular necrosis and renal failure, most likely attributable to toluene, following occupational exposure to thinners while cleaning a steel water tank. These adverse health effects have previously been reported following acute poisoning or intentional inhalation by drug abusers, but rarely in the occupational setting. Poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A timely introduction of renal replacement therapy is needed. Mild transaminitis, which is reversible, has been previously reported in the literature (10,32).…”
Section: Casementioning
confidence: 69%
See 1 more Smart Citation
“…A timely introduction of renal replacement therapy is needed. Mild transaminitis, which is reversible, has been previously reported in the literature (10,32).…”
Section: Casementioning
confidence: 69%
“…Rhabdomyolysis results either because of direct toluene muscular injury or prolonged immobility. They are usually seen with ingestion of toluene, but is reported in patients with thinner intoxication by inhalation (5,(30)(31)(32). Moreover, electrolyte abnormalities like hypokalemia and hypophosphatemia can also result in rhabdomyolysis and hence AKI.…”
Section: Casementioning
confidence: 99%
“…For example, excess circulating haem caused by solvent-induced rhabdomyolysis or haemolysis of red blood cells has been posited to cause acute tubular necrosis and renal failure [56]. In agreement with this hypothesis, Ngajilo and Ehrlich [57], in a recent study reported a case of rhabdomyolysis with acute tubular necrosis and renal failure in a steel water tank cleaner exposed to a mixture of organic solvents containing toluene, xylene, acetone, hexane, benzene and methylisobutyl ketone.…”
Section: Gr Up Sm Copyright  Ekpenyong Cementioning
confidence: 90%